PENGARUH DISCOUNT, MERCHANDISING, DAN HEDONIC SHOPPING MOTIVES TERHADAP IMPULSE BUYING - Manggiasih, Febrisa Pawestri; Widiartanto, Widiartanto; Prabawani, Bulan (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2015)
Febrisa.pm@gmail.comAbstrack: Retail’s consumers who tend to do an impulse buying. One of the retail in Semarang is Robinson. Basedon the preliminary study, there are some problems in there. The problems are the bad quality of the products, thebad display of the products, and consumers have less hedonic shopping motives. Total sales revenue whichdecreased in 2014. This research aims to determine the effect of discount, merchandising, and hedonic shoppingmotives towards impulse buying of the costumer of Robinson. Data collection techniques used in this research waspurposive sampling with 100 consumers as data samples. The data analysis was quantitative analysis used SPSSprogram version of 17. The analysis methode used were correlation test, determination, simple linear regression,multiple linear regression, T-test and F-test. The results of the analysis showed that there is positive effect andsignificant between discount, merchandising, and hedonic shopping motives towards impulse buying of the costumerof Robinson either partially or simultaneously. The variable discount is the greatest effect on impulse buying of thecostumer of Robinson than the merchandising and hedonic shopping motives. Discount can be enhanced by productchecking ,controlling, and improving product quality. Merchandising can be improved by adapting consumersneeds. Moreover, hedonic shopping motives can be improved by managing display shelf and doing some additionalfacilities.